Comportamento de sementes de Peltophorum dubium Sprengel (Taubert) em banco de sementes aéreo e do solo - Silva, Girlânio Holanda (2016)
The soil seed bank or aerial seed bank are important to the natural regeneration, assisting the ability of environmental recovery, because the seed banks are genetic source for the entry of new individuals in the ecosystem. The soil seed bank is composed by all seeds that remain viable in a given area of soil for variable periods. On the other hand, the aerial seed bank is another type of rarer natural regeneration strategy, characterized by prolonged retention of the mother plant fruits even after they have reached physiological maturity. Therefore, being aware of the importance of such regeneration strategies, this work aimed to study aspects of the behavior of aerial seed bank and burial seed bank of the species P. dubium. For the characterization of aerial seed bank, were collected, monthly, germination data of the P. dubium. The results indicated that the species P. dubium, forms aerial seed bank with short serotiny. For the evaluation of burial seed bank, bimonthly, germination data, seedling numbers, predation rate and seed water contente were collected. P. dubium seeds remain viable for up to 16 months in the soil, which allows the classification of the species as persistent seed bank forming.